Frequency of Post-Endoscopic Retrograde Cholangiopancreatography (ERCP) Complications - Asma Abdul Razzak; Muhammad Raza (Journal of Bahria University Medical and Dental College)
Objective: Endoscopic Retrograde Cholangiopancreatography (ERCP) is a highly technical procedure that carries some risks associated with it. It consolidates the utilization of an endoscope with X-ray to look at the biliary and pancreatic channels with the ability to intervene when indicated to address problems identified during surgery. This study aimed to determine the frequency Study Design & Setting: Cross-sectional study design at Dow Hospital Karachi. Methodology: The patients with the age ranging from 18 to 60 years who had endoscopies were taken from July 2020 to February 2021. All the pregnant patients and those who were unwilling to participate in the study were excluded from the study. The data were collected from the patients and they were kept under observation for 4 – 6 hours after ERCP to monitor the development of an immediate complication. The findings were recorded only at 48 hours of the procedure. Results: The age of the participants was 37±12 years on average. The complications were recorded with pancreatitis at 36% followed by 34.5% bleeding and 29% perforation. 92% of the procedures were successful. Conclusions: In conclusion, while ERCP is generally considered a safe and effective procedure, it is not without risks. The most common complications of ERCP are pancreatitis, bleeding, and perforation